2015
DOI: 10.5152/anatoljcardiol.2015.6130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of uninterrupted warfarin and bridging therapy using low-molecular weight heparin with respect to the severity of bleeding after dental extractions in patients with prosthetic valves

Abstract: Objective:The management of anticoagulated patients with warfarin during dental extraction is an intricate issue. We carefully designed the current study so that the amount of bleeding was measured with objective methods and the data from the same patient in different dental extraction appointments could be compared, eliminating the bleeding diathesis differences of patients.Methods:This prospective and controlled study was conducted in 36 adult patients with prosthetic valve requiring multiple tooth extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
0
8
0
7
Order By: Relevance
“…Every study had its protocol to assess bleeding outcome. A statistically significant difference in bleeding among groups was only observed in 2 studies: the first showing increased bleeding when bridging with LMWH [32] the second showing an increase in mild bleeding in VKA group when compared with no anticoagulation [33]. Only 4 patients across the 10 studies were reported to need hospitalization due to bleeding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Every study had its protocol to assess bleeding outcome. A statistically significant difference in bleeding among groups was only observed in 2 studies: the first showing increased bleeding when bridging with LMWH [32] the second showing an increase in mild bleeding in VKA group when compared with no anticoagulation [33]. Only 4 patients across the 10 studies were reported to need hospitalization due to bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 patients across the 10 studies were reported to need hospitalization due to bleeding. The number of teeth extracted was associated with an increased risk of bleeding in one study [32]. This relationship was not seen in two other trials [27, 29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found in a study that there is no association between the number of teeth extracted and postoperative bleeding status [62,68,69], except in one study [64]. In contrast to previous studies [65,66] and in line with others [61,67], a short interruption of oral anticoagulation did not seem to increase the risk of thromboembolic events in the 10 trials.…”
Section: Anticoagulants and Its Implications In Dentistrymentioning
confidence: 62%
“…Special measures were taken in most studies to handle the risk of bleeding, like reducing soft tissue and bone injuries and minimizing the need to raise a mucoperiosteal flap during the procedures. However, it must be noted that whether a mucoperiosteal flap raise was needed or not in dental extractions [61][62][63][64][65][66], the outcome remained in favour of maintaining oral anticoagulation. Also, in implant surgery, bleeding risk was not associated with the invasiveness of the surgery [67].…”
Section: Anticoagulants and Its Implications In Dentistrymentioning
confidence: 99%